2022
DOI: 10.1021/acsomega.2c04528
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Intermittent Ethanol Exposure Alters Behavioral Flexibility in Aged Rats Compared to Adult Rats and Modifies Protein and Protein Pathways Related to Alzheimer’s Disease

Abstract: Repeated excessive alcohol consumption increases the risk of developing cognitive decline and dementia. Hazardous drinking among older adults further increases such vulnerabilities. To investigate whether alcohol induces cognitive deficits in older adults, we performed a chronic intermittent ethanol exposure paradigm (ethanol or water gavage every other day 10 times) in 8week-old young adult and 70-week-old aged rats. While spatial memory retrieval ascertained by probe trials in the Morris water maze was not s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 92 publications
0
7
0
Order By: Relevance
“…To investigate the effect of CIEg during adolescence on behavioral flexibility in aged animals, we utilized a reversal paradigm in the water maze for 2 days (a total of eight trials), whereas the platform was rotated 180° from its initial location. As previously done ( Ho et al, 2022 ; Matthews et al, 2022 ), we treated the first two trials of reversal day 1 as learning trials and then analyzed percent change over the next six trials as a measure of behavioral flexibility, with these six trials grouped into two trial epochs. CIEg during adolescence impaired behavioral flexibility when animals were tested over 530 days later, as measured by latency to the submerged platform [two-way ANOVA with repeated measures, CIEg dose during adolescence (3) by reversal epoch (4), significant interaction of CIEg dose and epoch, F = 2.256, df(6,93), p = 0.0446].…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the effect of CIEg during adolescence on behavioral flexibility in aged animals, we utilized a reversal paradigm in the water maze for 2 days (a total of eight trials), whereas the platform was rotated 180° from its initial location. As previously done ( Ho et al, 2022 ; Matthews et al, 2022 ), we treated the first two trials of reversal day 1 as learning trials and then analyzed percent change over the next six trials as a measure of behavioral flexibility, with these six trials grouped into two trial epochs. CIEg during adolescence impaired behavioral flexibility when animals were tested over 530 days later, as measured by latency to the submerged platform [two-way ANOVA with repeated measures, CIEg dose during adolescence (3) by reversal epoch (4), significant interaction of CIEg dose and epoch, F = 2.256, df(6,93), p = 0.0446].…”
Section: Resultsmentioning
confidence: 99%
“…In humans, chronic EtOH abuse and withdrawal have been linked to marked neuropsychological impairments 22,[53][54][55][56] , with several studies highlighting cognitive deficits following moderate to extended periods of withdrawal 20,21,[57][58][59][60][61][62] . Contrastingly, in rodents, while some long-lasting effects on goal-directed control 3,63 and working memory 64 are noted, the evidence for impacts on reversal learning and attentional tasks has been inconsistent [24][25][26][27][28][29][30][31]65 . This discrepancy between human and animal studies may stem from longer EtOH use or polysubstance use 66 histories in humans and more complex cognitive demands of human tasks compared to rodent models.…”
Section: Discussionmentioning
confidence: 98%
“…Although the cognitive and neural mechanisms underlying chronic EtOH-induced reversal deficits are not yet fully understood, studies in humans have shown persistent disruption of reversal learning during protracted withdrawal from EtOH drinking [19][20][21][22] . In rodents, while EtOH exposure in adolescent subjects results in persistent cognitive deficits 23,24 , studies to date of chronic EtOH exposure and cognitive flexibility in adult rodents report relatively shortlasting (~< 2 weeks) deficits [25][26][27][28] , or no deficits 24,[29][30][31] . Thus, it remains unclear whether chronic EtOH exposure in adults causes a persistent deficit in flexible decision-making, despite evidence of such deficits in humans.Corticostriatal circuitry is implicated in decision flexibility 32,33 .…”
mentioning
confidence: 99%
“…Knockdown of hippocampal CACNA1C resulted in a significant reduction in ERK and CREB activation in the hippocampus and reduced synaptic plasticity in glutamatergic neurons [ 82 ]. In addition, PRKCD, RASGRP1, SYNCRIP, CSNK1E, and CBX3 were involved in the regulation of synaptic plasticity and were associated with cognitive impairment caused by neurological diseases [ 83 , 84 , 85 , 86 , 87 ]. The above information and results suggest that changes in the expression levels of these RNAs are associated with alterations in synaptic function.…”
Section: Discussionmentioning
confidence: 99%